Accounting information system: education and research agenda / Noor Azizi Ismail - Ismail, Noor Azizi (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
Revolution of information technology has changed many aspects of accounting practices, which resulted in greater demand for accountants with sufficient information technology (IT) knowledge and skills. Importantly, these changes have provided new and exciting research opportunities for accounting information system (AIS) researchers. This paper aims to address issues relating to both AIS education and research. It also attempts to provide guidance to AIS curriculum design and direction for AIS research. In terms of AIS education, this paper reveals that accounting programmes worldwide have not sufficiently integrated IT knowledge and skills into the curriculum, thus resulting in the inability to produce graduates that meet the current needs of businesses. In terms of research, the paper starts with a discussion on issues relating to definition, scope and category of AIS research. In general, while IT revolution has offered various research opportunities, AIS research has provided very limited contribution to accounting or information system research and practice. Towards this purpose, this paper provides several suggestions to researchers. First, AIS researchers need to view AIS in a broader perspective where the impact of technology on all areas of accounting, auditing, and taxation should be considered within the realm of AIS interest. Second, AIS researchers have to specialise in at least one other accounting area such as financial reporting, managerial accounting, audit or taxation, in addition to AIS domain, to produce high-quality research results. Finally, it is hoped that discussions brought forward by this paper would initiate and encourage debate among accounting professionals and academics and, in particular AIS lecturers, in order to strengthen current AIS curriculum to produce high-quality AIS research that can have a notable impact on the accounting profession and business practice.